2021
DOI: 10.1080/21645515.2021.1972709
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory-based surveillance in Latin America: attributes and limitations in evaluation of pneumococcal vaccine impact

Abstract: Disease surveillance data are needed to monitor trends in disease activity, inform decision-making in public health and evaluate disease prevention/control measures. The Sistema Regional de Vacunas (SIREVA) supports laboratory-based surveillance of invasive pneumococcal disease (IPD) in Latin American countries, providing information on identification, distribution, and anti-microbial susceptibility of pneumococcal strains. We estimated the proportion of pneumococcal meningitis and sepsis/bacteremia cases capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Considering these findings, ongoing surveillance is needed to monitor serotype dynamics and guide optimal PCV formulation. National passive surveillance systems such as SIREVA are valuable tools to monitor serotype distribution and antimicrobial resistance but do not provide disease burden data, so they are unsuitable for evaluating pneumococcal vaccines’ impact and could underestimate IPD incidence [ 186 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering these findings, ongoing surveillance is needed to monitor serotype dynamics and guide optimal PCV formulation. National passive surveillance systems such as SIREVA are valuable tools to monitor serotype distribution and antimicrobial resistance but do not provide disease burden data, so they are unsuitable for evaluating pneumococcal vaccines’ impact and could underestimate IPD incidence [ 186 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this is likely a gross underestimation, as has been shown with data of other pathologies from passive surveillance in Mexico. 54 This is because these data were based only on inpatient and emergency cases that were notified to the Mexico Health Secretariat and General Health Information Office, HZ is not a mandatorily notifiable disease, and HZ is often not captured as a primary diagnosis in the surveillance system.…”
Section: Discussionmentioning
confidence: 99%
“…It illustrates the potential magnitude of underestimation of pertussis, and there is considerable uncertainty in the estimates, as indicated by the broad 90% limits around the median values. In a study comparing the number of isolates of invasive pneumococcal disease reported to surveillance with the expected number of cases based on regional disease incidence data, Chile had the highest rate of reporting (43–83%) of the six Latin American countries in the study [ 41 ]. Other researchers have reported wide variations in pertussis prevalence between countries; in a study in 12 European countries conducted in 2007–2010, the percentage of adult patients presenting to primary care with acute cough who were found to have B. pertussis ranged from 0% in Italy to 6.2% in Sweden [ 42 ].…”
Section: Discussionmentioning
confidence: 99%